Smoking, Pain Intensity, and Opioid Consumption 1–3 Months After Major Surgery: A Retrospective Study in a Hospital-Based Transitional Pain Service. Issue 9 (3rd May 2017) - Montbriand, Janice J; Weinrib, Aliza Z; Azam, Muhammad A; Ladak, Salima S J; Shah, B R; Jiang, Jiao; McRae, Karen; Tamir, Diana; Lyn, Sheldon; Katznelson, Rita; Clarke, Hance A; Katz, Joel
Abstract: Introduction: The present study investigated the associations between smoking, pain, and opioid consumption in the 3 months after major surgery in patients seen by the Transitional Pain Service. Current smoking status and lifetime pack-years were expected to be related to higher pain intensity, more opioid use, and poorer opioid weaning after surgery. Methods: A total of 239 patients reported smoking status in their presurgical assessment (62 smokers, 92 past smokers, and 85 never smokers). Pain and daily opioid use were assessed in hospital before postsurgical discharge, at first outpatient visit (median of 1 month postsurgery), and at last outpatient visit (median of 3 months postsurgery). Pain was measured using numeric rating scale. Morphine equivalent daily opioid doses were calculated for each patient. Results: Current smokers reported significantly higher pain intensity ( p < .05) at 1 month postsurgery than never smokers and past smokers. Decline in opioid consumption differed significantly by smoking status, with both current and past smokers reporting a less than expected decline in daily opioid consumption ( p < .05) at 3 months. Decline in opioid consumption was also related to pack-years, with those reporting higher pack-years having a less than expected decline in daily opioid consumption at 3 months ( p < .05). Conclusions: Smoking status may be an important modifiable risk factor for pain intensity and opioid use after surgery. Implications: In a population with complex postsurgical pain, smoking was associated with greater pain intensity at 1 month after major surgery and less opioid weaning 3 months after surgery. Smoking may be an important modifiable risk factor for pain intensity and opioid use after surgery.